Status, Distribution and Conservation of the Asian Elephant (Elephas maximus) in Meghalaya - Marak, T. T. C. (Indian Forester, 2002)
Meghalaya is a small State (area 22429 km2, population 2.30 million, forest area 0.95 million ha, dense forest 9929 km2, open forests 9708 km2). The State Forest Department control 12% of forest area, the rest being managed by autonomous councils. There are 2 National Parks and 3 Wildlife Sanctuaries, protected area being 0.03 million ha which is proposed to be further extended. Elephant population cannot be considered without referring to neighbouring Assam and Bangladesh as there is inter-state movement of elephants. Estimates put the number at 1319 in 1998, while it was 2222 in 1993. Other estimate put the number at 2600. Death of elephants as well as humans also takes place. Compensation is paid. It is heavily in arrears and on April 1999 stood at Rs. 87.8 lakhs and even after payments made during 1999-2000, and proposed to be paid during 2001-2002 from State and Central funds is likely to be in arrears by Rs. 40.378 lakhs. The reserved and protected areas also cover unclassed areas where jhum cultivation prevails, so mananimal conflict takes place resulting in about 40% deaths of animals as well as humans, including forest staff on duty. There is need for extending reserve areas as elephants need large areas for movement as also to increase the staff and shifting cultivation has also to be checked and existing crops to be replaced by such crops as may be unattractive to elephants. Local people have to be involved and Development Committees framed with them on profit sharing basis, Research on population structure of elephants alternative crop patterns determination of home ranges seasonal habitat utilization pattern, habit assessment, movement pattern has also to be initiated.